Characterization and purification of protease extracted from two maturity stages of 'Noni' (Morinda citrifolia L.) fruit / Normah Ismail and Nurulain Abd Razak - Ismail, Normah; Abd Razak, Nurulain (Research Management Institute (RMI), 2014)
Protease was extracted from two maturity stages of noni fruits (Morinda citrifolia L.), unripe (stage 1) and ripe (stage 5). The crude extract was partially purified by acetone precipitation method followed by dialysis, gel filtration chromatography and freeze drying. Protein concentrations, proteolytic activity, molecular weight distribution, pH stability, temperature stability and storage efficiency of the resulting protease were evaluated. The unripe and ripe noni fruit contains 0.65 and 0.35% protein, respectively. Molecular weight of the proteases from both stages ranged approximately between 3 to 28 kDa based on the SDS-PAGE results. The optimum activity were at pH 7s and 6, temperatures of 40 and 50°C, respectively for proteases obtained from the unripe and ripe fruit. Analysis from the freeze dried protease indicated that protease from ripe noni fruits had higher protein concentration and specific activity compared to those from unripe fruit. However, it is more sensitive to pH and temperature and less stable during storage as it shows lower proteolytic activity compared to protease from unripe fruit. Based on its high proteolytic activity reaching up to 70.31 U/mg and storage stability (30% lost of activity), noni fruit could be an alternative source of plant protease.